Técnica DELPHI para análise de sistema informação: estudo de viabilidade - Kairalla, Anna Sylvia Silveira (1982)
This is a study on the viability of applying the DELPHI Technique to obtain the consensus opinion of the scientists and researchers of IPT concerning information systems. The following steps were taken: selection of participants, elaboration and application of questionnaires and analysis of the answers. The thoughts expressed reflect the opinion of the group of respondents. The Delphi method widely applied to a variety of study areas, is proved to be useful also in the Information field.